Music : the definitive visual history - 4 0 16; ElNaggar, Jennette,;Wilcox, Heather,;Blenkinsop, Ian,;Day, Kiku,;Grant, R. G.,;Ombler, Gary,;Leeney, Richard; 5 Smithsonian Institution (New York : DK Publishing, 2022)
A history of the progression of music since its prehistoric beginnings, reviewing not only Western music but also music from around the world. Includes profiles of influential musicians, a history of instruments, and a listing of key works for each genre.
Includes index.
Keywords: 2 -- 0; 6; History and criticism. -- Music;Musical instruments.;Musical form.;Popular music genres.;Composers.;Music.; 20; Chronologies.;Criticism, interpretation, etc.;History.;Informational works.;Illustrated works.;Chronologies.;Reference works